2019
DOI: 10.1002/ldr.3387
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of organic matter and microbial biomass after abandonment of degraded agricultural soils: the influence of climate

Abstract: After abandonment of agricultural lands (ongoing on 220 million hectares worldwide), degraded arable soils undergo self‐restoration and development towards natural ecosystems. We studied the linkage between microbial properties and density fractions of soil organic matter (SOM) during post‐agricultural restoration of former arable Phaeozems and Chernozems. The chronosequence study was conducted in two contrasting bioclimatic zones of European Russia: deciduous forest (Luvic Phaeozem) and dry steppe (Calcic Che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 63 publications
(112 reference statements)
0
14
1
Order By: Relevance
“…Chemical and microbial properties in the studied materials were interrelated, and therefore, the variation in microbial indices and the values of corresponding ecosystem services were partly explained by nutrients' and PTE contents. Commonly, soil C and N contents stimulate microbial biomass growth [68,69]; however, in our study, a positive correlation between C and N contents and qCO 2 was shown. Apparently, the energy costs for microorganisms to maintain their biomass under intensive input of C and N are too high.…”
Section: Microbial Properties Of the Materials In Relation To Nutrients And Pte Contentscontrasting
confidence: 73%
“…Chemical and microbial properties in the studied materials were interrelated, and therefore, the variation in microbial indices and the values of corresponding ecosystem services were partly explained by nutrients' and PTE contents. Commonly, soil C and N contents stimulate microbial biomass growth [68,69]; however, in our study, a positive correlation between C and N contents and qCO 2 was shown. Apparently, the energy costs for microorganisms to maintain their biomass under intensive input of C and N are too high.…”
Section: Microbial Properties Of the Materials In Relation To Nutrients And Pte Contentscontrasting
confidence: 73%
“…The variance in community composition (Figure 5c) demonstrated shifts in fungal community functions as stands aged. The vertical gradients in fungal diversity and composition are common due to the main input of organic materials starting from the topsoil (Chen et al, 2019a; Ovsepyan, Kurganova, de Gerenyu, & Kuzyakov, 2019; Uroz et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As said before, the study area is canyon-shaped, with horizontally extended mountains. Due to years of afforestation activities, there is significant forest cover on the mountains in the northwest portion of the basin; consequently, there is significant soil organic matter accumulation and low erodibility [42]. Less afforestation has been completed in the southeast mountains; thus, there is less plant root growth and distribution than in the north.…”
Section: Discussionmentioning
confidence: 99%